Ratio Legis Establishment of Execution and Supervisory Institutions Fulfillment of Child Rights in Family Law Due to Divorce - Ummu Salamah; Rachmi Sulistyarini; Dhiana Puspitawati; Thohir Luth (PT FORMOSA CENDEKIA GLOBAL, 2023)
Children are often neglected in fulfilling their rights in the family, especially if their parents die or divorce. In the Marriage Law and the Child Protection Act, arrangements have been made to fulfill children's rights if the child is abandoned by their parents or abandoned or if the parents are divorced through a court decision. However, parents, especially fathers or those who act as guardians for children, are often negligent and irresponsible in fulfilling their obligations even though there is a judge's decision in court. The purpose of this study is to examine the legal ratio for the establishment of an execution institution and supervisor for the fulfillment of children's rights in family law. The research method used is the normative legal research method. The excitement in this study is the establishment of an execution and supervisory institution in fulfilling children's rights. This institution is very necessary to provide protection, welfare, and justice for the fulfillment of children's rights in family law, especially protection for children due to divorce